Energy efficiency principle of tranditional Malay house / Nor 'Atikah Zainuddin - Zainuddin, Nor Atikah (Faculty of Architecture, Planning and Surveying, 2015)
The traditional Malay house is one of the richest components of Malay’s cultural heritage in Malaysia. Generally, the traditional Malay house is a reflection of the Malay community's way of living. With greater global awareness of the environment and a renewed perspective on contemporary Malaysian architecture, architects and designers are once again looking for tropical solutions in building design. One of the main characteristics of traditional Malay house is that they are designed with a deep understanding and respect for nature, but this design with- nature approach is no longer found in the modem buildings. The purpose is therefore to study the energy efficiency principle and element of Traditional Malay House such as building orientation, interior layout space, material of wall, natural ventilation and lighting, window designs, and stack effect on the roof design. The investigation was carried out through observations, questionnaire and some research visits. A comprehensive research was accomplished on the adaptation of Malay house architecture elements with selected the Perak, Melaka and Negeri Sembilan Traditional Malay House as the key study and one modem building. This study attempts to have recorded information for those who are interested and for the future generation because the traditional Malay house was evolved by the Malays over generations, adapting to their needs, culture and environment. This study is crucial to revive the awareness in the understanding and appreciation of the technique of the energy efficiency principle and element of Traditional Malay House adapted into modem building design.